Beyond the “inimitable” Goffman: from “social theory” to social theorizing in a Goffmanesque manner - Inglis, David; Thorpe, Christopher (Frontiers in Sociology, 2023)
Erving Goffman’s status as a great social scientist today seem relatively secure. Many commentators highlight his extraordinary capacities to pinpoint the fine-grained details of human behaviour in the ‘interaction order’. But if Goffman’s brilliance in this respect was deeply rooted in his various and interlocking personal, existential, social, and intellectual idiosyncrasies, and his intellectual practice is inimitable, the degree to which anyone else could, or should try to, imitate Goffman’s intellectual practice today, remains an open question. This is especially so when we consider that such practice was grounded in notably wide reading across disciplines and in world literature, a highly developed analytical manner that was inseparable from a notable literary talent in composing published texts, and an open-mindedness about the gathering of data sources in ways that some today find methodologically much too promiscuous. The paper initially considers these issues: the multiple ‘Goffmans’ that exegetes and commentators have identified; how such persons have claimed Goffman to be essentially of one or more theoretical persuasions; and how various social theorists have drawn upon Goffman’s work. It then moves on to argue that a Goffmanesque kind of social theorizing, is not only possible (if difficult) today, but also vital too. Such theorizing insists on the ongoing role of literary-intellectual and metaphorical ways of thinking and writing, at a time when these are becoming apparently less crucial in studies of human interaction. No matter how technologically advanced such studies may become, they still require some of the intellectual and literary flair that Goffman brought to his scholarly doings. Goffmanesque theorizing can inform new insights into various domains, including the very nature of social change